The Relationship of Social Capital With Job Satisfaction And The Quality of Nursing Care In Critical Care Nurses - Mohammad Ali Heidari Gorji; Fatemeh Naderifar; Ali Hesamzadeh; Nouraldin Moosavinasab; Ali Morad Heidari Gorji (ACHSM, 2023)
Introduction and Objective: Social capital is an important factor influencing job satisfaction and the quality of nursing care provided by nurses. This study aimed to examine the relationship between social capital, job satisfaction, and quality of nursing care among critical care nurses working in critical care wards (CCWs). Methods: A descriptive-analytical study was carried out in 2018, on nurses working in the critical care wards (CCWs) of Mazandarn University hospitals located in Sari, Iran. The study included 195 participants who completed a demographic questionnaire, Nahapiet and Ghoshal's Social Capital Questionnaire, Spector's Job Satisfaction Survey, and the Quality Patient Care Scale. The collected data were analyzed using both descriptive (Percentages, means, and standard deviations) and analytical statistics (Analysis of variance, Pearson's correlation coefficient and Univariate regression analysis). Results: The study's findings demonstrated a significant and positive correlation between social capital and both job satisfaction (p=0.001) and the quality of nursing care (p=0.001). Social capital was identified as an independent variable that accounts for 20% of the changes in job satisfaction and 41% of the changes in the quality of nursing care. Conclusion: This study highlights the importance of social capital in promoting job satisfaction and improving the quality of nursing care among CCW nurses. The findings demonstrate that social capital is a key factor that can significantly impact the quality of care provided to patients. Therefore, nursing managers must recognize the value of social capital and take active steps to promote it within their organizations.